Analisis Penerapan Manajemen Pelayanan pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Kapuas Hulu - Domi Domi (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was conducted at the Regional Drinking Water Company (PDAM) in Kapuas Hulu Regency. The aim of this research is to determine Service Management at the Kapuas Hulu Regency Drinking Water Company (PDAM). This research is a type of descriptive research with a qualitative approach, namely the author conducted interviews with informants who were directly involved. In this research, the informants were the heads and staff of PDAM employees who were directly involved in service activities. The author uses data collection techniques, observation, interviews and documentation. The results of this research are the services provided by the Drinking Water Company (PDAM) of Kapuas Hulu Regency, Dihalralpkaln kepaldal petugals Perusalhalaln Daleralh Alir Drinking (PDAlM) Kalbupalten Kalpuals Hulu Dalpalt, which has resulted in reversing the performance of public services in algalr permalsallalhaln permals. allalhaln recognizes turbid flow and the water does not flow and the installation is immediately resolved and the process of carrying out routine internal and external internal checking results in a process of recurrent quality problems.